Aluminum electrolysis derivative spent cathodic carbon for dendrite-free Li metal anode. (September 2020) - Liu, Tiancheng; Lin, Zezhou; Wang, Dong; Zhang, Man; Hu, Qiyang; Tan, Lei; Wu, Yingpeng; Zhang, Xi; Huang, Haitao; Wang, Jiexi
Abstract: Li metal anode is one of the most promising anodes for next-generation high-energy-density batteries. However, some lethal challenges, such as Li dendrite, inferior coulombic efficiency, and infinite volume change during repeated Li plating/stripping restrict its practical application. Although carbon-based materials are ideal hosts for Li deposition, unsatisfied lithiophilic property and vulnerable solid electrolyte interphase (SEI) film still remain unsolved. Herein, we report the fluorinated mesoporous carbon (FMC) nanosheets derived from spent cathodic carbon of aluminum electrolysis as a versatile dendrite-free current collector. Two types of C–F bonds are discovered in FMC. One is C(sp 2 )-F, which serves as lithiophilic site for Li nucleation with reduced barrier. The other is C(sp 3 )-F, which breaks to produce extra LiF during Li deposition, facilitating the formation of stable LiF-rich SEI film. The synergistically designed Li@FMC|LiFePO4 full cells demonstrate improved cycling performance with high coulombic efficiency. This work provides possibility for direct utilization of waste electro-carbon in energy storage application. Graphical abstract: A fluorinated mesoporous carbon (FMC) is developed to stabilize Li metal anode. The FMC contains two types of C–F bonds. One type is C(sp 2 )-F, which can induce lithiophilic Li nucleation with reduced barrier. The other type is C(sp 3 )-F bond with weakened C–F bond, facilitating the formation of stable LiF-rich SEI film. The lithiophilic Li nucleation with a stable SEI film realizes long-life Li metal anode. Image 1 Highlights: Spent cathodic carbon of aluminum electrolysis is used to prepare FMC. FMC contains two types of C–F bonds, C(sp 2 )-F and C(sp 3 )-F. C(sp 2 )-F serves as lithiophilic site for Li nucleation with reduced barrier. C(sp 3 )-F produces LiF during Li deposition, facilitating formation of stable SEI. Symmetric cells demonstrate ultra-low voltage hysteresis of 14 mV.